PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN PEMAHAMAN SANTRI PADA PEMBELAJARAN FIKIH TENTANG PENYELENGGARAAN JENAZAH DI PONDOK PESANTREN AL FALAH PUTERA BANJARBARU - Siti Rahmawati (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2017)
This study discusses the application of demonstration methods to improve students' understanding of fikih learning about the implementation of the corpse in boarding school Al Falah Putera Banjarbaru. The formulation of the problem in this research is how the implementation of demonstration method to improve the students' understanding on Fikih learning about the operation of the corpse at Pondok Pesantren Al Falah Putera Banjarbaru and what factors influenced it. The subject of research in the thesis is a class III students Wustha in Pondok Pesantren Al Falah Putera Banjarbaru. While the object in this study is the application of demonstrating method in Fikih learning, in this case, relates to the implementation of the corpse and the factors that influence in learning. In data mining, the author uses observation, interview, and documentation techniques. Data processing technique is done by editing, data classification, and data interpretation. Furthermore, it was analyzed by qualitative descriptive analysis and inductively drawn the conclusions. Based on the results of research known that the implementation of demonstration methods implemented on the learning of the corpse in Pondok Pesantren Al Falah Putera has been running very well so as to facilitate students in understanding learning Fikih, in this case, relates to the operation of the corpse. This is influenced by several factors, namely ustadz, santri factors related to intelligence, seriousness, and motivation are different, time allocation factors, factors of facilities and infrastructure and environmental factors. Keywords: Demonstration Method, Implementation of the Bodies, Pondok Pesantren